THE HISTORY OF THE GRAND DUCHY OF LITHUANIA AND CONTEMPORARY THEORIES OF INTERNATIONAL RELATIONS - Norkus, Zenonas (Politologija, 2015)
The paper explores the epistemic fruitfulness of the contemporary theories of modern relations for historical research about the relations between premodern polities. The application of the neorealist theory in such research is blocked by its assumption that its subject is international system, consisting of sovereign national states. However, there were no such states (and nations) in medieval Europe and most other places in premodern times. The concept of international society of H. Bull is not applicable to premodern polities because of its assumption that Westphalian peace treaty of 1648 was the date of birth of the international law and international society as historical reality. A. Wendt’s thesis that in the premodern times international politics was dominated by the Hobbesian culture of anarchy disregards historical evidence about the “Lockean” realities of the dynastic politics in the medieval Europe and other places. In the first part of the article, the corrections to remove these modernist and europocentric deformations are suggested. They include the replacement of the concepts of “international system” and “international society” by the broader notions of “interpolity system” and that of “interpolity society”, and the distinction between “sovereign politikes system/society” and “suzerain (imperial) polity system/society”, borrowed (with modifications) from M. Wight. Second part and third parts together constitute a case study about the changing roles and challenges of the Grand Duchy of Lithuania (GDL) as the subject of interpolity relations in XIII–XV centuries. The second part is about the rise of GDL from the polity playing the role of the barrier (but not that of buffer) polity, separating Central European and Eastern European interpolity systems and belonging to both of them, to the regional empire and suzerain polity of the Eastern European interpolity system by the early XVth century. However, Lithuanian hegemony in Eastern Europe lasted only very few years. After 1430, the Eastern European interpolity system was about to transform itself from the suzerain polity system into a multipolar sovereign interpolity system of the type that consolidated in the Central and Western Europe after 1648 and survived for 300 years. However, the political leadership of GDL failed to meet the challenge to maintain an emerging multipolar balance of power in this system. According to the unconventional account of the so-called “feudal war” (1431–1453) in the Great Duchy of Moscow by Alexander Zimin, there was real possibility to establish at least two Russian states in the lands ruled by the Muscovite princes. Great Novgorod was viable polity too, bearing promise of the protobourgeois and protodemocratic Russia. Another viable polity was created in Kazan by Tatars who have changed to sedentary life of agriculturalists, and were about to become the power, filling out the geopolitical space that in older times was held by Volga Bulgaria. However, mainly due to the pursuit by Jagiellonian rulers of GDL and Poland of the dynastic politics in the Central Europe, at least three windows of opportunity to preserve this interpolity system from its annihilation by rising Moscow empire were not used. Last of them was the opportunity to re-establish the independence of Great Novgorod in 1480. These failures of the Lithuanian statesmanship sealed the fate of the Eastern European interpolity system: its disappearance in the Moscow empire. So the history of Eastern European interpolity politics in the XIII–XVIII centuries is another case proving the finding of the recent research by Stuart J. Kaufman, William C. Wohlforth, Richard Little, David Kangi, Charles Jones, Victoria Tin-Bor Hui, Arthur Eckstein, Daniel Deudney, Williams Brenner that a long-lasting balance of power in a interpolity system is rather an exception than rule, the rule being the displacement of the multipolar or bipolar balance of power interpolity systems by empires.